Reconstruction 2D planar coordination using linear and nonlinear techniques - Dunn, M.; Wheat, J.; Miller, S.; Haake, S.; Goodwill, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Planar analyses of sports movements are commonly performed to quantify player movements from video. Lens distortions, which are common when using wide filming angles at competitive sports events, can influence the accuracy of reconstructed coordinates and derived metrics. This study describes a planar reconstruction method that accounts for lens distortion and compares reconstruction accuracy to 2D-DLT. The planar reconstruction method yielded improved reconstruction accuracy in wide angle filming conditions experienced at an international tennis event.